2021
DOI: 10.1016/j.prnil.2020.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Ga-68 PSMA PET/CT for diagnosis and grading of local prostate cancer

Abstract: Background We aimed to evaluate the utility of prostate-specific membrane antigen (PSMA) PET/CT for the detection of local disease within the prostate. Methods This is a retrospective review of a single-center experience evaluating intraprostatic detection rates compared with final histopathology in a radical prostatectomy (RP) population. Seventy-two patients had PSMA PET/CT scan performed as part of their primary staging. Intraprostatic PSMA PET/CT avidity was assesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Recently, 68Ga-PSMA-PET/CT has been suggested to improve the clinical stadiation of high-risk PCa and disease recurrence [ 7 ]; at the same time, PSMA PET/CT has been proposed for the diagnosis of primary intraprostatic cancer [ 15 ]. The presence of focal uptake on PSMA-PET/CT, the standardised uptake value (SUVmax) and the maximal dimensions of PET-avid lesions have been correlated with the presence of csPCa [ 20 , 21 ]. There is a range of proposed cutoffs to detect csPCa from SUVmax 3.15 to up SUVmax 9.1 [ 22 , 23 ]; the concordance between preoperative PSMA PET/TC evaluation (SUVmax, dimension of the lesion), and definitive prostate specimen ranges from 81.2% (24) to 96% [ 24 , 25 , 26 , 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, 68Ga-PSMA-PET/CT has been suggested to improve the clinical stadiation of high-risk PCa and disease recurrence [ 7 ]; at the same time, PSMA PET/CT has been proposed for the diagnosis of primary intraprostatic cancer [ 15 ]. The presence of focal uptake on PSMA-PET/CT, the standardised uptake value (SUVmax) and the maximal dimensions of PET-avid lesions have been correlated with the presence of csPCa [ 20 , 21 ]. There is a range of proposed cutoffs to detect csPCa from SUVmax 3.15 to up SUVmax 9.1 [ 22 , 23 ]; the concordance between preoperative PSMA PET/TC evaluation (SUVmax, dimension of the lesion), and definitive prostate specimen ranges from 81.2% (24) to 96% [ 24 , 25 , 26 , 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, it does not accurately represent the molecular state of the tumor cells or their biological characteristics. 1 , 2 , 3 , 4 , 5 Serum PSA is often measured as high in men without PCa or low in advanced PCa. Many other biological markers have been studied to compensate for this and PSA mRNA has been proposed as a novel marker.…”
Section: Discussionmentioning
confidence: 99%
“…However, it does not accurately evaluate the biological characteristics of prostate cancer cells, and there is a need to develop better biological markers to assess the progression of prostate cancer. 1 , 2 , 3 , 4 , 5 In particular, as the treatment for metastatic PCa is diversified, there is increased interest in the development of biomarkers to predict treatment responsiveness.…”
Section: Introductionmentioning
confidence: 99%
“…Initial utilisation primarily focused upon its role in the detection of disease recurrence following the curative-intent treatment of the primary cancer by surgery or radiotherapy, and also as a tool for primary staging [1] , [2] , [3] . More recently, PSMA PET has an evolving role as a diagnostic tool to characterise prostate cancer within the gland [4] , [5] , [6] , [7] , [8] . Several provocative studies have indicated the potential for PSMA imaging in conjunction with multiparametric magnetic resonance imaging (MRI) of the prostate to triage those men who could be potentially reassured and monitored, rather than proceed to diagnostic biopsy [6] , [7] , [9] .…”
Section: Introductionmentioning
confidence: 99%